2013
DOI: 10.1292/jvms.12-0119
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Feline Orbital Aspergillosis Due to <i>Aspergillus udagawae</i> and <i>A. viridinutans</i>

Abstract: ABSTRACT. Aspergillus udagawae and A. viridinutans are members of the section Fumigati; both cause invasive aspergillosis in humans. These two Aspergillus species are discriminated from A. fumigatus by molecular methods. Herein, we report two cases of feline orbital aspergillosis, one caused by A. udagawae and the other by A. viridinutans. To our knowledge, Case 1 represents the first reported case of treatment of A. udagawae with a high dosage of itraconazole, and Case 2 represents the first reported case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 11 publications
3
14
1
1
Order By: Relevance
“…Thus, risk factors additional to orbital lysis are clearly necessary for the establishment of mycotic orbital disease in cats. Previous studies have found that A. fumigatus infections were confined to the SNC, while cases of SOA were caused by cryptic species, particularly A. felis (Barrs et al, 2013;Barrs and Talbot, 2014;Declercq et al, 2012;Kano et al, 2008;Kano et al, 2013). Imaging findings presented here are consistent with this putative role for fungal species in disease outcome.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Thus, risk factors additional to orbital lysis are clearly necessary for the establishment of mycotic orbital disease in cats. Previous studies have found that A. fumigatus infections were confined to the SNC, while cases of SOA were caused by cryptic species, particularly A. felis (Barrs et al, 2013;Barrs and Talbot, 2014;Declercq et al, 2012;Kano et al, 2008;Kano et al, 2013). Imaging findings presented here are consistent with this putative role for fungal species in disease outcome.…”
Section: Discussionsupporting
confidence: 87%
“…Molecular identification revealed two new isolates of A. udagawae from Australia and the USA. These, in addition to two previous isolates reported in Japan establish A. udagawae as the second most common cause of feline SOA (Kano et al, 2008;Kano et al, 2013). A. udagawae is the most common cryptic species to cause invasive pulmonary aspergillosis in humans (Vinh et al, 2009).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations